PENDUGAAN POTENSI POPULASI DAN EKOLOGI JELUTUNG (Dyera costulata (Miq.) Hook. F) DI HARAPAN RAIN FOREST (HRF-PT REKI) JAMBI - Rahila Junika Tanjungsari; Ervizal A.M. Zuhud; Iskandar Z. Siregar (Department of Forest Resources Conservation and Ecotourism - IPB University, 2016)
Jelutung (Dyera costulata) is a native species from Sumatra and Borneo. D. costulata has various benefit, for human and environment. The main use of jelutung is the latex as industrial raw materials. Jelutung population in natural habitat has decreased and the product is no longer available in market. The objectives of this research were (1) to identify population of jelutung in Harapan Rain Forest-PT Restorasi Ekosistem Indonesia (HRF-PT REKI), (2) to analyze habitat characteristics of D. costulata on HRF. The study was conducted in May-June 2015 at HRF-PT REKI, Batanghari District, Jambi. Data were collected by interview and vegetation analysis with sample plot of 2 ha. Result this study showed, D. costulata stand condition in HRF was abnormal. Jelutung tree diameter class is a class at most a diameter of 40 cm - 60 cm by 26 individuals D. costulata can grow in temperature condition 23oC -28oC and soil condition that are very acidic and poor of nutrient. But, species richness around habitat jelutung a relatively high. In conclussion jelutungs of the study could be used to local conservation and management for sustainable used.Keywords: ecology, jelutung, potency